2014
DOI: 10.3389/fnins.2014.00277
|View full text |Cite
|
Sign up to set email alerts
|

Auditory stream segregation using bandpass noises: evidence from event-related potentials

Abstract: The current study measured neural responses to investigate auditory stream segregation of noise stimuli with or without clear spectral contrast. Sequences of alternating A and B noise bursts were presented to elicit stream segregation in normal-hearing listeners. The successive B bursts in each sequence maintained an equal amount of temporal separation with manipulations introduced on the last stimulus. The last B burst was either delayed for 50% of the sequences or not delayed for the other 50%. The A bursts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 73 publications
4
32
2
Order By: Relevance
“…The analysis was focused on a subset of the recording electrodes, namely an auditory (central location, El.1; corresponding to the center in Nie et al, 2014) and a centro-parietal (14,27,28; corresponding to Twomey et al, 2015) set. Depicted potentials show averages across each set of electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was focused on a subset of the recording electrodes, namely an auditory (central location, El.1; corresponding to the center in Nie et al, 2014) and a centro-parietal (14,27,28; corresponding to Twomey et al, 2015) set. Depicted potentials show averages across each set of electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…one in the equidistant layout of EasyCap, equal to Cz; corresponding to the center in Nie et al, 2014). The CPP signal was based on a set of centro-parietal electrodes (El.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that some, but not all, implant recipients, using their speech processors, can segregate auditory streams on the basis of electrode location and other stimulus parameters (Chatterjee et al, 2006, Cooper and Roberts, 2007, Cooper and Roberts, 2009, Harris and Kamke, 2014. In normal hearing subjects , comparisons of mismatch negativity and cognitive components of cortical potentials show that preattentive processes can provide a basis for discriminating between different auditory streams that differ in spectral content (Nie et al, 2014 ). These authors speculate that CI recipients, in whom spectral information may be degraded, might have to rely on more active attentional processes, assumed to be cortical.…”
Section: Discussionmentioning
confidence: 99%
“…This positive-going deflection is often discussed as a possible variant of the P300 component, reflecting updating working memory (Hajcak, Dunning & Foti, 2009; also see Donchin & Coles, 1988). The P300 is known to be a neurocognitive index of novelty detection and attentional capture, and its amplitude is strongly dependent on the stimulus context and task demands (Nie, Zhang, & Nelson, 2014). Because Zhang et al (2010) also observed an N400 component in their experiment, they propose that the LPP may in fact be a P300 component reflective of updating working memory.…”
mentioning
confidence: 92%